Interpersonal Communication of People with Hearing Impairments in Building Social Interaction in the Perumnas Simalingkar Community: English - Khalisah Salsabila; Nurhanifah (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2026)
This study aims to gain an in-depth understanding of the communication processes, barriers encountered, and adaptive strategies employed by people with hearing impairments in establishing social interactions within the Perumnas Simalingkar community. The study employs a qualitative descriptive approach, utilizing data collection techniques such as interviews, observation, and documentation. The informants in this study consist of people with hearing impairments as well as individuals in the surrounding community who interact frequently with them. The results indicate that interpersonal communication among people with hearing impairments occurs adaptively, relying on nonverbal communication such as sign language, facial expressions, and body movements, and is supported by written communication. Communication barriers identified include differences in the understanding of symbols, limitations in interacting with new individuals, and a lack of environmental understanding of sign language. To overcome these barriers, people with hearing impairments employ various forms of adaptation, such as the use of written communication, clarification strategies, and the utilization of communication technology. Additionally, an inclusive and empathetic environment plays a crucial role in fostering effective communication..